Present Status Diversity of Medicinal Plants of Keechangulam Forest Reserve in Mullaitivu District of Sri Lanka - Sathiyaseelan, V. (Central Environmental Authority Sri Lanka, 2015)
Sri Lanka is one of the smallest but biologically most diverse country. The flora of Keechangulam forest reserve in the Mullaitivu District was surveyed for medicinal plants over a period of three months (January 2013- March 2013), using a belt transects method. Interviews we also held with traditional physicians surrounding the surveyed area to identify ethno-botanical information about the medicinal plants flora of the forest. The predominant forest type observed in the study are was Dry Mixed Evergreen forest. A total of 252 medicinal plant species belonging to 60 families were recorded during the study. This includes 130 trees, 52 herbs, 55 shrubs, 9 lianas, and 6 stragglers comprised of perennials (78%), annual (20%), and biennials (2%). Among the medicinal plant species recorded, 13 species were identified as native species, I endemic species, and one critically endangered species. Out of the 252 medicinal plant species, 10 species were identified to be poisonous, 20 species are used for diabetic mellitus, 12 in vadha diseases, 15 in treating skin diseases, and 16 for respiratory disorders. It was observed that 32 species are collected for medicinal purposes by the physicians surrounding the forest. Rauvolfia serpentia, Salvadora persica, Erythroxylum monogynum, Andrographi spaniculata, and Salacia reticulata were recorded as economically useful medicinal plants in the survey area. The primary threats to the flora of medicinal plants of the Keechangulam Reserve include illegal logging, encroachment, and lack of knowledge on identification of medicinal plants. Due to these kinds of threats many native medicinal plants of Keechangulam Reserve are in the verge of extinction. It is suggested that necessary steps should be taken to declare the Keechangulam forest area as a natural reserve for medicinal plants.
Keywords: Diversity; Keechangulam forest; Medicinal plants; status